2008
DOI: 10.1590/s1806-83242008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oral health and its impact on quality of life among adolescents

Abstract: The aim of this study was to assess oral health status and its relationship with quality of life. A household population, cross-sectional study was carried out; participants were between 15 and 17 years of age (n = 247) and were examined by two calibrated dentists. Socio-economic status was classified according to ANEP-ABIPEME criteria. Clinical examinations to observe DMFT, CPI and Dean indices were performed as per WHO criteria. The Significant Caries Index (SiC) was used to evaluate polarization of the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
61
4
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 11 publications
12
61
4
14
Order By: Relevance
“…Another study observed the oral health status and its relationship with quality of life of adolescents aged 15-17 years and found average OHIP-14 of 3.95 [25], while in the present study, this value was 12.39. As in this study, this study found a positive and statistically significant correlation between higher OHIP score and presence of decayed teeth [25].…”
Section: Discussioncontrasting
confidence: 70%
“…Another study observed the oral health status and its relationship with quality of life of adolescents aged 15-17 years and found average OHIP-14 of 3.95 [25], while in the present study, this value was 12.39. As in this study, this study found a positive and statistically significant correlation between higher OHIP score and presence of decayed teeth [25].…”
Section: Discussioncontrasting
confidence: 70%
“…For adolescents, relationships between peers are important components of their perceptions of health and quality of life. 21 There were statistically significant differences between the reports of the mothers and adolescents on the FL and SWB subscales. However, in determining the level of agreement of the pairs individually, significant moderate agreement was found for the items "difficulty eating or drinking hot or cold foods" (FL subscale) and "avoided smiling or laughing when around other adolescents" (SWB).…”
Section: Discussionmentioning
confidence: 88%
“…1 Associations between oral diseases and oral health-related quality of life (OHRQoL) in children and adolescents have been described in several cross-sectional studies. 2,3,4,5 Albeit very helpful in investigating the potential causes of a health condition, prospective cohort studies in this area are still scarce. 6 In addition, social determinants of health such as socioeconomic status and family environmental characteristics have been linked to oral health in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%